Increasing military capability through information and communication - Bernardino, L.; Marsili, M. (Conference Proceedings of the DeSRA 2016 Conference, 2016)
The scope of this abstract is to pursue and increase the quality levels of the military instrument to enhance the effectiveness, operational capabilities and overall employability by providing a timely information representation and a catchy and tailored visualization and communication support. The impact of information and communication on civilian/military maritime operations should be addressed in a social and political perspective. The success of communication, both indoor and outdoor, is essential for achieving goals. A fully informed and favorable outdoor and indoor environment supports and facilitates the achievement of military objectives. Communication must be multimedia, multiplatform and multilevel. Communication to be strength, must represent information in a simply and clear way through short text elements integrated with interactive visual representations: they capture at best the audience attention, without compromising the efficacy of the information content to be transmitted. Online availability through user-friendly and intuitive interface, enabling a positive user experience, is strongly recommended. Language should be natural for not military audience, and glossary should be available. Information should be manually categorized for not military audience. Communication results should be measured through a validation and verification process.